Endothelial TRPV4–eNOS coupling as a vital therapy target for treatment of hypertension. (28th January 2022) - Mao, Aiqin; Zhang, Peng; Zhang, Ka; Kan, Hao; He, Dongxu; Han, Xiping; Wang, Zhiwei; Tang, Chunlei; Ma, Xin
Abstract : Background and Purpose: Reduced NO levels and activity are signs of endothelial dysfunction, which is important in mediating BP changes. Previously, we demonstrated that transient receptor potential channel V4 (TRPV4) could form a functional complex with other proteins to mediate vasodilation in endothelial cells (ECs). But how TRPV4 interacts with the NO pathway in larger arteries requires further exploration. Experimental Approach: We used single‐cell RNA‐sequencing to find the CD106 + TRPV4 high NOS3 high ECs. The TRPV4–eNOS interaction was verified by co‐immunoprecipitation and immuno‐FRET, and their binding site was found by site‐directed mutagenesis. Endothelium‐specific TRPV4 knockout (TRPV4EC −/− ) mice were used to study the effect of the TRPV4–eNOS interaction on BP. A small molecule, JNc‐463, was designed through molecular docking technology. Key Results: We uncovered CD106 + TRPV4 high NOS3 high ECs in the mouse aorta, which could regulate vasodilation via a TRPV4–eNOS interaction, and were essential to regulate BP. The TRPV4–eNOS interaction markedly decreased during the process of hypertension. We further attempted to identify molecules involved in the TRPV4–eNOS interaction and developed a small‐molecule drug, JNc‐463, which could increase the TRPV4–eNOS interaction to enhance vasodilation and exert antihypertensive effects in mice. Conclusion and Implications: This is the first study integrating single‐cell RNA‐Seq, single‐cell functional study and drug screening in aorta. We identified a subpopulation of CD106 + TRPV4 high NOS3 high ECs, in which an impaired TRPV4–eNOS interaction was important in the progress of hypertension, and we designed a small molecule, JNc‐463, to improve the impaired TRPV4–eNOS interaction in hypertension.